2018
DOI: 10.1093/aje/kwy106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Etiology-Specific Diarrhea Associated With Linear Growth Faltering in Bangladeshi Infants

Abstract: Childhood diarrhea in low-resource settings has been variably linked to linear growth shortfalls. However, the association between etiology-specific diarrhea and growth has not been comprehensively evaluated. We tested diarrheal stools collected from the Performance of Rotavirus and Oral Polio Vaccines in Developing Countries study from 2011 to 2013 in Dhaka, Bangladesh, by quantitative polymerase chain reaction for a broad range of enteropathogens to characterize diarrhea etiology and examine the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 30 publications
5
56
2
Order By: Relevance
“…Chakraborty (2009) reported that the odds of receiving any food at <4 months and at 4-6 months of age were higher, 1.4 times (aOR 1.40, 95% CI: 1.20-1.60) and 1.18 times (aOR 1.18, 95% CI: 1.02-1.40) in stunted children than in nonstunted children, respectively. Schnee et al (2018) identified the association between stunting and diarrhea was pathogen-specific. The diarrhea caused by Cryptosporidium, Campylobacter, and Shigella associated with stunting in the first year of life and persisted up to 24 months, but not viral diarrhea (Schnee et al, 2018).…”
Section: Breastfeedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Chakraborty (2009) reported that the odds of receiving any food at <4 months and at 4-6 months of age were higher, 1.4 times (aOR 1.40, 95% CI: 1.20-1.60) and 1.18 times (aOR 1.18, 95% CI: 1.02-1.40) in stunted children than in nonstunted children, respectively. Schnee et al (2018) identified the association between stunting and diarrhea was pathogen-specific. The diarrhea caused by Cryptosporidium, Campylobacter, and Shigella associated with stunting in the first year of life and persisted up to 24 months, but not viral diarrhea (Schnee et al, 2018).…”
Section: Breastfeedingmentioning
confidence: 99%
“…Schnee et al (2018) identified the association between stunting and diarrhea was pathogen-specific. The diarrhea caused by Cryptosporidium, Campylobacter, and Shigella associated with stunting in the first year of life and persisted up to 24 months, but not viral diarrhea (Schnee et al, 2018). (Schnee et al, 2018).…”
Section: Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand there was no evaluation of the prevalence of other pathogenic or parasitic organisms, so it is not certain that the presumptive Campylobacter isolated in samples was the definite cause of wasting and/or diarrhoeal prevalence seen here. A few studies have reported mixed infections of Campylobacter and viral pathogens and their associations with infant morbidities [32,85]. This presence of Campylobacter alongside the carriage of multiple pathogens may correlate as a proxy for infants with greater overall levels of exposure to enteric pathogens in their environment; this in turn may associate with those with poor growth and/or wasting.…”
Section: Plos Onementioning
confidence: 99%
“…Over time, molecular diagnostics were developed from single-gene qPCR assays to multiplex reactions (1014) and to multi-assay, multi-sample arrays that can be operated in parallel on a single chip or card (1519). Specifically in the field of enteric pathogen detection, a TaqMan Array Card (TAC) was developed by Liu and colleagues (15, 16) and subsequently used in several studies to estimate pathogen-attributable diarrhea burdens (3, 4, 20), as well as the impact of enteric pathogens on child growth (21–23) and vaccine uptake (24, 25). However, despite advances in the throughput of molecular detection of pathogens, costs associated with broad multi-target molecular assays still pose a barrier to their widespread use in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%